2005
DOI: 10.1104/pp.104.056507
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analyses Identify 10 Classes of the Protein Disulfide Isomerase Family in Plants, Including Single-Domain Protein Disulfide Isomerase-Related Proteins  

Abstract: (J.-M.S., R.J.)Protein disulfide isomerases (PDIs) are molecular chaperones that contain thioredoxin (TRX) domains and aid in the formation of proper disulfide bonds during protein folding. To identify plant PDI-like (PDIL) proteins, a genome-wide search of Arabidopsis (Arabidopsis thaliana) was carried out to produce a comprehensive list of 104 genes encoding proteins with TRX domains. Phylogenetic analysis was conducted for these sequences using Bayesian and maximum-likelihood methods. The resulting phylogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
201
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(203 citation statements)
references
References 79 publications
0
201
0
2
Order By: Relevance
“…While the donor(s) of oxidizing equivalents for interchain disulfide bond formation remain to be identified, ER-located oxidoreductases (Houston et al, 2005) and plant homologs of the yeast and mammalian Ero proteins (Dixon et al, 2003) are possible players in the pathway leading to the covalent assembly of glutenin subunits.…”
Section: Discussionmentioning
confidence: 99%
“…While the donor(s) of oxidizing equivalents for interchain disulfide bond formation remain to be identified, ER-located oxidoreductases (Houston et al, 2005) and plant homologs of the yeast and mammalian Ero proteins (Dixon et al, 2003) are possible players in the pathway leading to the covalent assembly of glutenin subunits.…”
Section: Discussionmentioning
confidence: 99%
“…In the Arabidopsis thaliana genome, there are either 22 (Houston et al, 2005) or 12 PDI-like genes (Lu and Christopher, 2008), depending on whether the more distantly related adeno-sine 5′-phosphosulfate-like and quiescin-sulfhydryl oxidase gene families are included. In plants, PDIs have been implicated in several biological processes, including the unfolded protein response (Lu and Christopher, 2008) and folding storage proteins during the biogenesis of protein bodies from the ER in the seed endosperm (Li and Larkins, 1996;Okita and Rogers, 1996;Shimoni et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Houston et al (2005) showed that BiP and ZmPDIL5-1 proteins accumulate differentially in fl oury-2 maize following the onset of zein protein accumulation 15 days after pollination (DAP) and Shank et al (2001) reported an increase in CCT enzyme activity 16 days after pollination in this mutant. Unfortunately, wild-type maize shows no differential accumulation of BiP or ZmPDIL5-1 and CCT activity appears to drop off 10 to 16 days after pollination.…”
Section: Figure 2 Schematic Representation Of the Involvement Of Uprmentioning
confidence: 99%